Magnetic resonance imaging of the human placental cotyledon: Proposal of a novel cotyledon appearance score. (January 2019) - Otake, Yuko; Kanazawa, Hidenori; Takahashi, Hironori; Matsubara, Shigeki; Sugimoto, Hideharu
Abstract: Objective: To determine the magnetic resonance imaging (MRI)-detectable morphology of the placental cotyledon, we proposed the first cotyledon appearance scores on MRI. Cotyledon appearance scores consist of two subscores: orthogonal and parallel cotyledon appearance scores. These represent cotyledon appearance orthogonal or parallel to the placental thickness, respectively. Study design: This retrospective study was approved by the institutional review board of our hospital. A total of 51 placentas were studied. Two MRI specialists independently evaluated the two cotyledon appearance subscores at various gestational ages. Scores were related to gestational age. Results: Cotyledons were not evident in the 2nd trimester, but were identified in the 3rd trimester. Cotyledon appearance subscores increased according to gestational age, with subscores showing good inter-observer agreement. Conclusion: Cotyledon appearance scores determined that placental cotyledons became evident on MRI, suggesting that placental maturity progressed with gestational age. These placental MRI findings may serve as references for placental MRI to detect placental abnormalities.